GIS analysis for flood hazard mapping: Case study Segamat, Johor, West Malaysia - Mohd., Mohd. Safie (2006)
Although a natural disaster is the consequence of the combination of a natural hazard and human activities, human vulnerability, caused by the lack of appropriate emergency management, leads to financial, structural, and human losses. Malaysia is fortunate to be freed from natural disaster such as earth quake, volcano and typhoon. However, the most severe natural disaster experiencing in Malaysia is flood. Two major type of flood occur in this country are monsoon flood and flash flood. The monsoon flood occur mainly from Northeast Monsoon which prevails during the months of November to March with heavy rains to the east coast states of the Peninsula, northern part of Sabah and southern part of Sarawak. This study aims to highlight the potential usage of GIS techniques and analysis for floodplain and flood hazard mapping. The study area is the Segamat District, Johor, Southern part of West Malaysia. By using Autocad Map 2004 and Arcview 3.1, several GIS analysis using spatial analysis have been performed for floodplain mapping. The results obtained can be used by Local authorities or other flood related organizations for flood management, mitigation and control.